Glycerol mediated low temperature synthesis of nickel nanoparticles by solution reduction method - Singh, Kalpana; Kate, Kunal H.; Chilukuri, V. V. Satayanarayana; Khanna, P. K. (Journal of Nanoscience and Nanotechnology, 2011)
Phase pure Nickel nano-particles were synthesized by in-situ generation of nickel hydrazine hydrate complex (Ni-HH) followed by its decomposition in an alkaline glycerol medium. The synthesis can be performed in an open beaker with or without the use of surface protective reagents. By using the present method, Ni nano-particles can be prepared in large scale. The black nano-powders so-obtained were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), selected area electron diffraction (SAED), Scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Fourier transform infra-red (FTIR) spectroscopy and thermal analysis (TGA). XRD and SAED analysis revealed that the synthesized particles were pure crystalline nickel with FCC structure.
Keywords: Chemical Reduction; Nano-Particles; synthesis; Transition Metal; XRD